2023
DOI: 10.1108/ec-07-2023-0345
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal and lateral stability control for autonomous vehicles in curved road scenarios with road undulation

Zhizhong Guo,
Fei Liu,
Yuze Shang
et al.

Abstract: PurposeThis research aims to present a novel cooperative control architecture designed specifically for roads with variations in height and curvature. The primary objective is to enhance the longitudinal and lateral tracking accuracy of the vehicle.Design/methodology/approachIn addressing the challenges posed by time-varying road information and vehicle dynamics parameters, a combination of model predictive control (MPC) and active disturbance rejection control (ADRC) is employed in this study. A coupled contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…As a result, we derived an equation to estimate the maximum lateral offset distance based on the offset angle and speed at which the truck is travelling. Mecheri et al investigated how the lane width, shoulder width, and road cross-sectional reallocation affect the driver's lateral positioning, lateral position variability, and driving speed [25]. They found that reductions in lane width caused drivers to drive their vehicles in the center of more advanced roads.…”
Section: Road Designmentioning
confidence: 99%
“…As a result, we derived an equation to estimate the maximum lateral offset distance based on the offset angle and speed at which the truck is travelling. Mecheri et al investigated how the lane width, shoulder width, and road cross-sectional reallocation affect the driver's lateral positioning, lateral position variability, and driving speed [25]. They found that reductions in lane width caused drivers to drive their vehicles in the center of more advanced roads.…”
Section: Road Designmentioning
confidence: 99%